Dependence of changes in hematological and integrative parameters in patients with chronic viral hepatitis C on the received antiviral therapy - A. H. Lishnevska; M. D. Chemych (Kazimierz Wielki University, 2020)
A total of 287 patients were treated with various antiviral therapy options: group I - basic (pathogenetic and symptomatic) therapy, group II - pegylated interferon in combination with ribavirin, group III - pegylated interferon with ribavirin and sofosbuvir, group IV - direct-acting antivirals. Patients with chronic viral hepatitis C (CVHC) before the start of treatment showed a decrease in platelet counts, segmented neutrophils and an increase in level of lymphocytes, bilirubin content, alanine aminotransferase activity, aspartate, transferrinase (practice), with a comparison group (practically virus-free patients) <0.05. After 4 weeks of receiving interferon-containing therapy, a further decrease was observed: leukocyte count, erythrocyte count, platelet count; ALT, AST and gamma-glutamyltranspeptidase (GGTP) activity; increased erythrocyte sedimentation rate (ESR), bilirubin content, and bilirubin activity p< 0.05. Patients who received direct-acting antivirals (DAAs) had a decrease in: erythrocyte count, total bilirubin content, ALT activity, AST, GGTP; increase in sed rate and the AST/ALT ratio, p <0.05. After 12 weeks of treatment, patients treated with pegylated interferon were diagnosed with a decrease in platelet count, erythrocyte count, and leukocyte count (with the exception of patients with dual therapy that experienced the slight increase of the leukocytes) with hemoglobin content, p <0.05. Also, in the group II subjects compared with week 4 decreased: the content of bilirubin and creatinine, the activity of ALT, AST, GGTP, while the De Ritis ratio increased (p <0.05). Patients in group III had lower GGTP activity than at 4 weeks and lower ALT and AST values compared with the onset of  antiviral therapy (p <0.05). Patients receiving DAAs experienced a decrease in hemoglobin content; no changes in biochemical parameters at this stage compared with the previous one were established. The investigated integrative indicators suggest changes in the immune system of patients, in particular the prevalence of cellular immunity over the humoral link and the predominance of the autoimmune component. Patients with dual and triple PVT regimens had more pronounced changes compared to patients receiving DAAs.